Ефект обтиску в задачах про коливання попередньо навантажених оболонок - Григоренко, Я.М.; Беспалова, О.І.; Урусова, Г.П. (Видавничий дім "Академперіодика" НАН України, 2008)
The paper presents a technique for studying the natural frequencies of nonthin inhomogeneous shells of revolution acted by static axisymmetrical loads. The technique is based on a nonclassic shell model that takes all the kinds of transverse deformation (transverse shears and reduction across a wall thickness) into account. The efficiency of allowing for the reduction across the wall thickness is illustrated by the example of a substantially inhomogeneous nonthin cylindrical shell with complicated structure.